The Protein C System – How Complex Is it? - Marlar, Richard A. (Thrombosis and Haemostasis, 2001)
Since the initial discovery of activated protein C (APC) and protein C (PC), subsequent findings have demonstrated that the protein C anti-thrombotic mechanism (anticoagulant and profibrinolytic) is very complex and convoluted, involving a multitude of other proteins and interactions with cell surfaces (1, 2). The PC system may be as complex as the coagulation scheme and other defense mechanisms. In recent years, investigations into ancillary functions of the PC system have identified interactions with some of these defense mechanisms in particular the inflammatory response (1, 3). Investigation of this highly complex system is no simple task.The number of proteins directly or indirectly involved in the PC system is growing, with several playing dual roles in the presence or absence of cells (1-5). Because of its complexity, the PC system can be broken down into functional subsets: cell-surface activation of protein C, the anticoagulant mechanism, the long-recognized but poorly-understood fibrinolytic response, and the shutdown mechanisms of the PC system. In the analysis of in vitro mechanisms of the PC pathway, care must be taken in the final interpretation of and application to the in vivo activities. We must weigh the importance of the apparent “minor” interactions with the perceived “major” roles these proteins play (5, 6). Any cursory review of these functions delineates the complexity of the system as a whole. The complex nature of the PC system reinforces how important good research is to the realization of our understanding of this functioning system. Because of the complexity of the system, the following questions must be meticulously addressed: What is the importance of each of the interactions? And what is the physiological role of these seemingly “minor” interactions of components in the regulation of the PC system?